Fertility and Hatchability of Pekin and Muscovy Duck Eggs and Performance of Their Ducklings (Progressive Agriculture, 2013)
Five hundred ten duck eggs of Pekin and each of Muscovy duck eggs were incubated to determine fertility and hatchability. The eggs were cleaned and stored at 18-21oC for 6 days prior to setting in the incubator. The eggs were incubated in a forced-draft electric incubator and the hatching performances were recorded. Ninety Pekin and ninety Muscovy day-old ducklings were randomly selected from the hatched ducklings for a growth trial. Each breed was divided into three replications and each replication had 30 ducklings. They were reared up to 10 weeks of age. Fertility of Muscovy duck eggs tended to be higher (P>0.05) than that of Pekin duck eggs. Hatchability of Pekin egg on fertile egg was higher (P